2021
DOI: 10.3390/agronomy11071313
|View full text |Cite
|
Sign up to set email alerts
|

Combined Application of Biochar and Lime Increases Maize Yield and Accelerates Carbon Loss from an Acidic Soil

Abstract: Biochar, an ecologically friendly soil amendment, is suggested for large-scale field application for its multiple potential benefits, including carbon sequestration, crop yield improvement, and the abatement of greenhouse gas emissions. However, it is unknown how effective it is in changing soil properties and its associated yield improvement when biochar is co-applied with lime in acidic soil. Here, we examined the effects of two different biochars, i.e., rice husk biochar (RHB) and oil palm empty fruit bunch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…In the initial stage of our pot study, the emission of CO 2 flux was highest on day 5 from all the amended soil due to the speedy mineralization of soil organic carbon [68]. This result is consistent with the findings of Mosharrof et al [69]. According to Fidel et al [70], the daily emission of CO 2 was changed because of the variation of density of root and biomass of plants, resulting in the labile soil organic carbon variation.…”
Section: Impact Of Treatments On Changes In Soil Co 2 Emissionsupporting
confidence: 91%
“…In the initial stage of our pot study, the emission of CO 2 flux was highest on day 5 from all the amended soil due to the speedy mineralization of soil organic carbon [68]. This result is consistent with the findings of Mosharrof et al [69]. According to Fidel et al [70], the daily emission of CO 2 was changed because of the variation of density of root and biomass of plants, resulting in the labile soil organic carbon variation.…”
Section: Impact Of Treatments On Changes In Soil Co 2 Emissionsupporting
confidence: 91%
“…In summary, it can be preliminarily concluded that Al 3+ stress has become a major threat to root growth in pomelo orchards. In general, crop roots indeed improved, while crop yield also significantly increased after the application of soil amendments, that is, lime and biochar, to neutralize Al 3+ (Demchak & Smith, 2019; Hale et al, 2020; Hin et al, 2020; Li, Cui, et al, 2019; Mosharrof et al, 2021). Conversely, studies also found that short‐term lime application was not sufficient to completely solve soil acidification (Li, Conyers, et al, 2019; Li, Cui, et al, 2019; Li, Li, et al, 2019; Zhang, Yang, Hsu, et al, 2021; Zhang, Yang, Muneer, et al, 2021), which might be the cause of the lack of a significant difference in yield among the different treatments in the first 2 years (2019 and 2020) (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, SOC was the most critical factor consistently affecting bacterial and fungal community structure. Shortly after the application of carbon-rich biochar, the unstable carbon in the biochar will rapidly act on soil microorganisms and promote their growth and reproduction [28][29][30]. Furthermore, some small molecules in biochar act as potential regulators that alter soil microbial activity and community structure [31].…”
Section: Biochar Improved the Microenvironment Of Saline-sodic Soilsmentioning
confidence: 99%